Relation of intraoperative bile culture to the postoperative morbidity in hepatopancreatic and biliary surgeries - Nisar, Sabina; Jan, Umar; Gilkar, Ishfaq Ahmad; Ali Bangri, Sadaf; Reddy, Sudershan (International Surgery Journal, 2019)
Background: The reported incidence of bacteria in bile is extremely variable 8%-42%. Several authors have been able to correlate the bacteria cultured from bile at operations with those subsequently causing wound infections and septicemia in postoperative period. Methods: This study was a prospective study conducted in Department of Surgical Gastroenterology at Sher-i-Kashmir Institute of Medical Sciences from July 2016 to June 2018. A total of 100 patients were included in study. Results: Mean age of the patients was 43.7±15.01, The most common organism found in our study was Escherichia coli (E. coli) and Klebsiella pneumoniae (K. pneumoniae) in 33.9%, E.coli and Enterococcus faecalis 21%, The monomicrobial infection was due to E coli 11.3%, The patients with bactibilia had more of wound infection 54.8% and intra-abdominal collections 17.7%, most common organism from bile was E. coli and K. pneumonia and same organisms were also cultured from wound sites. Conclusions: The preoperative intervention group should be considered potentially infected, requires careful operative technique to avoid spillage of bile on wound surfaces to decrease infection rates and morbidity.